Clinical impact of idiopathic pulmonary fibrosis on SARS-CoV-2 patient outcomes: a comprehensive analysis in the pre-vaccination era - Tamimi, Omar; Safdar, Zeenat; Siddiqui, Nadia; Nisar, Tariq; Gotur, Deepa (Frontiers in Medicine, 2025)
IntroductionOur retrospective study aimed to evaluate the impact of idiopathic pulmonary fibrosis (IPF) on the clinical outcomes of COVID-19 admissions using data from the 2020 nationwide inpatient sample (NIS).MethodsWe performed multivariate adjustment for baseline comorbidities and demographics after univariate screening.ResultsAmong the 1,018,915 adults hospitalized with COVID-19 in 2020, 910 were also diagnosed with IPF. Patients admitted with both COVID-19 and IPF had a higher risk of mortality compared to those without IPF [adjusted OR 1.87 (95% CI 1.13-2.70), p < 0.01]. Additionally, patients with both conditions had higher odds of requiring mechanical ventilation [adjusted OR 1.66 (95 % CI 1.13–2.42) p = 0.01] and needing mechanical ventilation within the first 24 h of admission [adjusted OR 1.87 (95% CI 1.013–3.39) p = 0.04]. IPF patients incurred higher mean total hospitalization charges [140,790 vs. 79,045, adjusted difference + 60,577 (SD ± 52,460)] and had a longer mean length of stay [11.2 vs. 7.5 days, adjusted difference 3.3 days longer (SD ± 2.0)] compared to the non-IPF cohort (p = 0.02).DiscussionOur findings suggest that IPF significantly worsens the clinical outcomes of COVID-19 hospitalizations, leading to increased healthcare utilization and costs. Further studies are needed to study this subpopulation during the postvaccination era to understand the effects on patient outcomes and to explore potential targeted interventions for improving prognosis in patients with both COVID-19 and IPF.